Alia Antropologia di una comunità dell'entroterra siciliano - Chiarelli, Brunetto (Firenze University Press, 2002)
In the spring of 1995, during works for the rehabilitation of a wall that closed the grotto of the Old Cemetery in the Sicilian village of Alia, the skeletal remains of the victims of the cholera outbreak of 1837 that had been rapidly interred here were brought to light. From that moment on, the Alia project was developed without interruption, analysing the biological evolution of the local population by exploiting study methods characteristic of different anthropological disciplines, such as skeletal biology, population genetics and biodemography. The book renders account of research completed and in progress carried out by academics from the Universities of Florence, Palermo, Parma, Cagliari, Turin and Göttingen.